Kinsenoside inhibits the inflammatory mediator release in a type-II collagen induced arthritis mouse model by regulating the T cells responses. Issue 1 (December 2016) - Hsiao, Hung-Bo; Hsieh, Chang-Chi; Wu, Jin-Bin; Lin, Ho; Lin, Wen-Chuan
Abstract Background Anoectochilus formosanus has been used as a Chinese folk medicine and is known as the "King of medicine" in Chinese society due to its versatile pharmacological effects such as anti-hypertension, anti-diabetes, anti-heart disease, anti-lung and liver diseases, anti-nephritis and anti-Rheumatoid arthritis. Kinsenoside is an essential and active compound ofA. formosanus (Orchidaceae). However, the anti-arthritic activity of kinsenoside has still not been demonstrated. In the present study, we confirmed that the kinsenoside treatment rheumatoid arthritis induced by collagen-induced arthritis in mice. Methods Male DBA/1 J mice were immunized by intradermal injection of 100 μg of type II collagen in CFA. Kinsenoside was administered orally at a dose of 100 and 300 mg/kg once a day after 2nd booster injection. Paw swelling, arthritic score and histological change were measured. ELISA was used to measure cytokines including tumor necrosis factor alpha (TNF-α), interleukin-10 (IL-10), interleukin-17 (IL-17) and interferon-γ (IFN-γ) in the splenocyte according to the manufacturer's instructions. Results Compared with model group, kinsenoside significantly inhibited paw edema and decreased the arthritis score and disease incidence. Histopathological examination demonstrated that kinsenoside effectively protected bone and cartilage of knee joint from erosion, lesion and deformation versus those from the CIA group. Kinsenoside also decreased IL-1β, TNF-α, and MMP-9 expression, and increased the expression of IL-10 in inflamed joints. The administration of kinsenoside significantly suppressed levels of TNF-α, IFN-γ, and IL-17, but increased concentrations of IL-10 in the supernatants of each of the splenocytes in CIA mice compared with that in the H2 O-treated mice with CIA. Using flow cytometric analysis, we demonstrated that kinsenoside increases the population of CD4+ CD25+ regulatory T cells, thereby inhibiting the Th1 cell and B cell populations. Anticollagen IgG1 and IgG2a levels decreased in the serum of kinsenoside-treated mice. Conclusions These results suggest that the administration of kinsenoside effectively suppressed inflammatory mediators' production and bone erosion in mice with collagen-induced arthritis showing the potential as an anti-arthritis agent.